Electron Streaming Effect Associated With the Elekta Unity Anterior Imaging Coil - Powers, Marcus; Baines, John (Frontiers in Physics, 2022)
The presence of the static field in magnetic resonance guided radiation therapy (MRgRT) systems such as the Elekta Unity MR-Linac (MRL influences charged particle motion, due to the Lorentz force, in and around patients. Consequently, for the Unity, changes to out-of-field dose (OFD) relative to conventional linacs occur due to the electron streaming effect (ESE) and spiralling contaminant electrons (SCE). This work investigates OFD associated with irradiation of the anterior MR imaging coil which is in situ for all treatments on the Unity. Film measurements and Monaco simulations were performed to quantify the magnitude of OFD at the superior and inferior ends of the coil, as a function of coil tilt relative to the beam direction. The dependence of OFD on field size, and the RED assigned to the coil and surrounding air, are reported. Doses at both coil ends were clinically significant, with nearly 23.0 % of the Dmax dose to water being recorded for the largest field (8.0 × 22.0 cm2) and 6.8 % for the smallest field (3.0 × 3.0 cm2). Monaco simulations of OFD agreed with film to within 5.0 %, when appropriate calculation conditions were set. OFD decreases as coil tilt is reduced and there is no evidence of ESE when the coil is horizontal. Clinically, the potential magnitude of cranio-caudal streaming dose from a tilted coil necessitates the use of appropriate shielding. A clinical case involving coil induced ESE during treatment of a lesion in the right angle is presented. The planning-based investigation revealed ESE doses associated with the coil and an immobilization vacuum bag can be clinically significant.